The Influence Of Principals’ Servant Leadership And Teacher Engagement On Teacher Intention To Stay In The Schools Of Maldives - Ali, Abdul Latheef (2023)
The high teacher attrition rate in the Maldives is a major concern for the public education sector. This study investigated the impact of principals' servant leadership on teachers' intention to stay and the role of teacher engagement as a mediator in this relationship. The study found that servant leadership behaviors of school principals significantly influence teachers' intention to stay, while teacher engagement plays a mediating role in this relationship. This finding is consistent with previous research in other cultural and demographic contexts. The study also found that creating a positive and engaging work environment for teachers can foster their intention to stay. By implementing servant leadership practices, school principals can enhance teacher retention, productivity, and overall school effectiveness. These findings offer valuable insights for policymakers and educational practitioners in the Maldives and can contribute to the ongoing efforts to improve the public education system. The Maldives has been experiencing a gradual increase in teacher attrition since 2019, which has posed a significant challenge to the public education sector. This study investigated the impact of principals' servant leadership on teachers' intention to stay, and the role of teacher engagement as a mediator in this relationship. The study found that servant leadership behaviors of school principals significantly influence teachers' intention to stay, while teacher engagement plays a mediating role in this relationship. This finding is consistent with previous research in other cultural and demographic contexts.